The relationship between media multitasking and creativity: a multi-test, multi-method analysis - Chen, Shi; Bai, Han; Zeng, Zhicheng; Yu, Quanlei; Zhao, Qingbai (Frontiers in Psychology, 2024)
Media multitasking is widespread, yet its relationship with creativity remains unclear. This study employs a combination of measures, including the media multitasking questionnaire, alternative uses task (AUT) for divergent thinking, Chinese compound remote association task (CCRAT) for convergent thinking, and a creative problem-solving task, to examine the relationship between media multitasking and creativity. Extreme values grouping [one standard deviation above or below the mean of the media multitasking index (MMI)], median value grouping, and regression analysis were used to explore the relationship between media multitasking and creativity. The results revealed the following findings: (1) across the three analysis methods, there was no significant relationship between media multitasking and performance on the AUT task. However, within the range of one standard deviation above or below the mean of the MMI, media multitasking showed a significant positive correlation with fluency, flexibility, and total scores on the AUT task. (2) Media multitasking significantly predicted the accuracy of responses on the CCRAT task positively. (3) Media multitasking significantly predicted lower scores on the applicability of creative problem-solving tasks.